Alkaline Decomposition of Solid Solution of Ammonium-Sodium Jarosite with Arsenic - Víctor H. Flores; Francisco Patiño; Antoni Roca; Mizraim U. Flores; Iván A. Reyes; Martin Reyes; Hernán Islas (Metals, 2022)
In this study, a solid solution of arsenical ammonium-sodium jarosite, with the approximate formula [(NH4)0.72 Na0.06(H3O)0.21]Fe3(2.52)(SO4)1.85 (AsO4)0.15 [(OH)4.41 (H2O)1.59], was synthesized. The precipitate particle main size was 38 µm, with spherical morphology. A decomposition reaction in alkaline media was carried out; this decomposition comprised three stages: an induction period, a progressive conversion and a stabilization period. The process was controlled by the chemical reaction, and the progressive conversion period was consistent with the shrinking core model. The dissolution reactions of the compound in NaOH media were characterized by an ash layer formed by solid residues made of Fe(OH)3 with adsorbed arsenate surrounding an unreacted core through which Na+, NH4+ and SO42− ions diffused into the solution. At the same time, OH− ions diffused from the solution into the reaction front until the core disappeared, indicating the end of the reaction.